2020 XXIX International Scientific Conference Electronics (ET) 2020
DOI: 10.1109/et50336.2020.9238240
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impact of the Number of Devices on Communication Interference in Bluetooth Low Energy

Abstract: In this paper, the impact of the number of devices on the communication interference in Bluetooth Low Energy (BLE) is studied. The reliability of BLE communication in real life is partially revealed, by investigating the channel hopping features inside. The reliability drawbacks inside BLE are raised and they serve as the basis for future improvement. The reliability is analyzed in terms of the time of the first collision and total collision probability. The result shows that both channel selection algorithms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Testing has shown that when a vehicle with a token is driven on a nearby unmeasured road, the token can be detected up to a non-negligible distance. Therefore, the recommendation is to consider a suitable location for the detection point [31,32]. Testing also suggests the recommendation not to stop a vehicle with a token near a BLE scanner due to scanner flooding and the associated reduction in the reliability of detecting other tokens in vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Testing has shown that when a vehicle with a token is driven on a nearby unmeasured road, the token can be detected up to a non-negligible distance. Therefore, the recommendation is to consider a suitable location for the detection point [31,32]. Testing also suggests the recommendation not to stop a vehicle with a token near a BLE scanner due to scanner flooding and the associated reduction in the reliability of detecting other tokens in vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Their model predicts up to 65% collision with 40 communicating pairs as shown in figure 1. Hallez et al [23] compare the performance of channel selection algorithms 1 and 2 (CSA#1 and CSA#2) in different interfering environments. They show that although the collision probability with the new channel selection algorithm is almost halved compared to CSA#1, nevertheless, with only ten active piconets, the probability of collision in a channel is more than 70%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The AFH allows BLE devices to hop within the 2.4 GHz frequency band, trying to avoid the spectrum occupied by Wi-Fi [5]. It is based on channel selection algorithms (CSAs), which synchronize the hopping process for BLE devices within the same BLE connection [6]. It has been proved that, with some improvements, the CSAs are able to detect and avoid Wi-Fi interference [7], [8].…”
Section: Introductionmentioning
confidence: 99%